Analisis Beban Kerja Jabatan Fungsional Pustakawan pada Unit Penunjang Akademik Perpustakaan Universitas Riau - Thamrin Hasan (Jurnal Gema Pustakawan, 2025)
This study analyzes the workload of functional librarians at the Library Technical Implementing Unit (UPA) of Riau University. The aim is to identify the librarians' main duties and responsibilities, analyze the level of workload, and provide strategic recommendations for optimizing job allocation. The research employed a mixed-method approach using a case study design, combining quantitative and qualitative data. Data collection involved observation, in-depth interviews, and document analysis. The research findings indicate that: 1) The main duties and responsibilities carried out by librarians at the UPA Library of Riau University are grouped into four major functions: collection processing/technical services, user/patron services, education and information literacy development, and library management and administration. 2) The workload of librarians at the UPA Library of Riau University is not proportionally distributed, with the majority of time (45%) consumed by technical tasks such as cataloging and classification. This gap creates an overload that triggers psychological challenges and hinders strategic duties such as self-development, information literacy education, and library promotion. 3) The study recommends three main steps: (a) Task redistribution to create a more balanced division of labor. (b) Competency improvement and technology adoption, such as automation, to reduce the manual workload. (c) Performance evaluation based on outcomes to encourage a focus on tasks with greater impact. This study contributes by presenting specific empirical data and tailored solutions for the UPA Library of Riau University, which can serve as a foundation for management in enhancing library efficiency and service quality.